2006
DOI: 10.1007/s00330-006-0336-9
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical experience with oral manganese (CMC-001) for liver MR imaging

Abstract: Recently, a new oral liver-specific manganese-based MR agent (CMC-001) has been introduced. This contrast medium is delivered to the liver in high concentrations in the portal vein and very low doses in the hepatic artery, as only small amounts of manganese enter the general circulation. It is taken up by the hepatocytes and excreted in the bile. Our initial experience with the new MR contrast medium in a variety of patients is reported. A total of 20 patients (11 males and 9 females) were studied with MR imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The observed AE after the administration of 1.6 g of CMC-001 were related to the high ion-content resulting in gastrointestinal discomfort, diarrhoea and nausea. Although not serious, AE after CMC-001 were numerous and clearly of higher frequency than those reported by others, being a factor that could potentially inhibit a widespread use (83)(84)(85)(86). Therefore we initiated the investigation presented in study IV, with the aim to investigate whether lowering the dose of MnCl 2 tetrahydrate could result in fewer AE but with a sufficient diagnostic imaging quality.…”
Section: Studies III and Ivmentioning
confidence: 99%
“…The observed AE after the administration of 1.6 g of CMC-001 were related to the high ion-content resulting in gastrointestinal discomfort, diarrhoea and nausea. Although not serious, AE after CMC-001 were numerous and clearly of higher frequency than those reported by others, being a factor that could potentially inhibit a widespread use (83)(84)(85)(86). Therefore we initiated the investigation presented in study IV, with the aim to investigate whether lowering the dose of MnCl 2 tetrahydrate could result in fewer AE but with a sufficient diagnostic imaging quality.…”
Section: Studies III and Ivmentioning
confidence: 99%
“…Without knowing what minimum oral dose would be necessary to show the differential enhancement of peripheral nerves in this model of neuropathic pain, we chose to give a series of increasing oral doses. Manganese chloride has previously been given safely to human subjects at an oral dose of 1.6 g per ~70‐kg individual . We used this precedent as a starting point for our dosing, with an equivalent 1 × dose of 2.29 mg manganese chloride per 100 g body weight.…”
Section: Resultsmentioning
confidence: 99%
“…By adding for example vitamin D 3 and an amino acid, the uptake of manganese can be increased in the same way as with calcium (20). How much the uptake increases is not known, but THOMSEN et al demonstrated uptake in 12 consecutive volunteers (19) and 20 consecutive patients (18). Orally administered CMC-001 is excreted solely by bile; increased blood levels of manganese were not found (19), whereas 15% of intravenously administered manganese (mangafodipir trisodium) was eliminated by urine in 24 hours and 59% by feces in 5 days (2).…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration offers some practical advantages, too, as it is not necessary to administrate it in the scanner room, or at the hospital. Further, it contains only nutritional ingredients, which reduce the risk of side effects (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation